Enhanced photocatalytic activity of TiO2 activated by doping Zr and modifying Pd. Issue 36 (23rd March 2016) - Huang, Shaolong; Yu, Yanlong; Yan, Yabin; Yuan, Jixiang; Yin, Shougen; Cao, Yaan
Abstract : The photocatalytic activity of 4-CP degradation is apparently enhanced by doping Zr and modifying Pd in TiO2 (TiO2 –Zr–Pd) under visible light irradiation. Abstract : A series of TiO2 photocatalysts introduced with Zr and Pd (TiO2 –Zr–Pd x ) are synthesized via a sol–gel method. It is revealed that Zr 4+ ions are doped into TiO2 lattice in the substitutional mode and Pd 2+ ions exist as –O–Pd–O– species on the surface of TiO2 . The energy level of the substitutional doped Zr 4+ ions and –O–Pd–O– surface species are located about 0.15 eV below the conduction band and 0.4 eV above the valence band, respectively. Moreover, the band structure of TiO2 –Zr–Pd x can be further adjusted by changing the amount of Pd 2+ ions. Owing to the synergistic effect of Pd and Zr, the response is extended into the visible region and the photogenerated charge carriers are separated effectively. Therefore, TiO2 –Zr–Pd x samples exhibit improved photocatalytic activity, compared with TiO2 –Zr and TiO2 –Pd under both UV and Vis irradiation.